MSMEs Taxation System and Bookkeeping for MSMEs in Sunggal District, Deli Serdang Regency - Wiliam, Wiliam; Tina, Agus; Saputri, Khana; Katharina, Ninta; Aruan, Deasy Arisandy; Amir, Afriza; Fitriano, Andre (Wahana Jurnal Pengabdian kepada Masyarakat, 2024)
MSMEs (Micro, Small and Medium Enterprises) are businesses that have a fairly high role, especially in Indonesia, which is still classified as a developing country. With the large number of MSMEs, there will be more job opportunities for the unemployed. In addition, MSMEs can be used as a source of income, especially in rural areas and low-income households. Lack of knowledge about the taxation and bookkeeping system for MSMEs is one of the reasons why MSME actors in Sunggal District, Deli Serdang Regency are reluctant to calculate, pay and report their income. In the socialization carried out by the PKM team, it was found that almost all MSME actors in Sunggal District, Deli Serdang Regency did not understand and did not know how to calculate, pay and report taxes on MSMEs. In addition, MSME actors also still do not use a good bookkeeping system to support MSME business records. The PKM team intends to carry out PKM activities with an approach method through counseling and socialization regarding the taxation and bookkeeping system for MSMEs. Through this PKM activity, it is hoped that it will be beneficial for MSME in Sunggal District, Deli Serdang Regency in the form of increasing knowledge and understanding related to the taxation and bookkeeping systems for MSME.